USE OF INFORMATION-COMMUNICATION TECHNOLOGIES IN THE IMPROVEMENT OF CIVIL PROTECTION DOCUMENTS IN ECONOMIC FACILITIES - Kosimov Jurabek Sodikovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article presents the existing problems in the preparation and maintenance of documents in the field of civil protection at the economic facilities of the Republic of Uzbekistan, ways of widespread use of information and communication technologies in their improvement, existing problems, and proposals for their positive solution.